The Effect of Annealing on the Structural and Optical Properties of the Bismuth (III) Iodide (Bii3) Thin Film Prepared by Vacuum Thermal Evaporation in Order to Lead Free-Perovskite Solar Cells Fabrication - Ihsas, Mohammad Ismail; Rasooli, Faiqa (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
In this study, effect of annealing temperatures in room, 100 and 200 C0 on the structural and optical properties of Bismuth (III) iodide (BiI3) thin films is investigated. The deposition process of the specimens was done by physical vapor deposition method on FTO substrate. The samples were prepared at 200 nm thickness. The structural properties, and optical absorption spectra of samples were measured by XRD and UV–Vis spectrophotometer. The Urbach energy and band gap of the samples were obtained by absorption spectrum fitting Tuac methods. The results showed that by increasing the annealing temperature up to 100 C0, the crystallinity of samples increased, the band gap and Urbach energy decreased about 1.60 and 0.17 eV, respectively. The results show that by increasing the annealing temperature up to to 200 C0, the band gap and Urbach energy increase. Studies on the structural and optical properties of thin films, show that BiI3 can be used as an active layer in lead-free perovskite solar cells.